2017
DOI: 10.4269/ajtmh.16-0666
|View full text |Cite
|
Sign up to set email alerts
|

The Arc of Human Immunodeficiency Virus Capacity Development: Insights from a Decade of Partnership for Medical Education in Zambia

Abstract: Abstract. Zambia and other sub-Saharan nations suffer from a critical shortage of trained health-care professionals to combat the human immunodeficiency virus/acquired immunodeficiency syndrome crisis. The University of Maryland and the Zambian Ministry of Health have partnered over the past decade to develop health-care capacity among physicians, nurses, and community health workers. We describe novel interventions to train health-care workers at all levels and argue that our collaboration represents a succes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…A strength of our project was the unique expertise available at UTH as a result of, among other things, a robust training program for ID physicians [32,33] and strong collaboration among ID physicians, ID pharmacists, and microbiologists at UTH and the University of Maryland Baltimore (UMB). This interdisciplinary group has also collaborated to study antibiotic prescribing patterns at UTH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A strength of our project was the unique expertise available at UTH as a result of, among other things, a robust training program for ID physicians [32,33] and strong collaboration among ID physicians, ID pharmacists, and microbiologists at UTH and the University of Maryland Baltimore (UMB). This interdisciplinary group has also collaborated to study antibiotic prescribing patterns at UTH.…”
Section: Discussionmentioning
confidence: 99%
“…UTH is a 1655-bed teaching hospital that trains medical students, nurses, and pharmacists and serves as a referral hospital for the country. UTH trains Zambian physicians in advanced HIV medicine and infectious diseases through a collaboration between the Ministry of Health, UTH, the University of Zambia, and UMB [32,33].…”
Section: Patients and Study Sitementioning
confidence: 99%
“…Although antimicrobial treatment selection is largely driven by the limited formulary and availability of many antimicrobials in resource-limited areas, the results of this study highlight discrepancies that exist between clinical practice, Zambian infectious diseases guidelines, and national guidelines from more developed parts of the world. [13][14][15][16][17][18][19] For example, the 2008 Zambian Standard Treatment Guidelines recommend using benzyl penicillin or ampicillin (plus chloramphenicol) for the treatment of meningitis in adults, while 2004 IDSA Practice Guidelines for the Management of Bacterial meningitis recommend vancomycin plus a thirdgeneration cephalosporin. [20] Evidence is cited in the IDSA guidelines for cephalosporins- namely that they have demonstrated superiority in clinical trials against Haemophilus influenzae meningitis, when compared to chloramphenicol.…”
Section: Discussionmentioning
confidence: 99%
“…The models of care included in our analysis [urban adherence groups, community adherence groups, home antiretroviral therapy (ART) delivery (through the Community HIV Epidemic Control; CHEC model), and mobile ART] were indeed more expensive than conventional care. This is not surprising, as each of the models layered additional services on top of existing conventional care [2]. We are pleased that in the time since our article was submitted for publication, new models of care have been introduced in Zambia that may marginally reduce costs to the provider, due primarily to the reduction in number of clinic visits required in those newer models [3][4][5].…”
mentioning
confidence: 94%
“…The authors found that conventional care was least expensive in terms of direct clinical service and medication costs, whereas mobile ART, CAGs, UAGs, and CHEC were more expensive, in that order.We appreciate this detailed costing analysis of DSD models in Zambia. At the University of Maryland Baltimore, we have nearly two decades of experience in the provision of medical/technical service delivery in Zambia [2]. Based on community-based approaches demonstrated to improve HIV case-finding and linkage [3], provide high-quality care [4], and improve retention in adult ART programs [5], we developed and implemented the CHEC model [6], which provides home delivery of ART and was one of the models evaluated in this analysis.…”
mentioning
confidence: 99%